Corrosive environments in municipal waste composting facilities: mechanisms, corrosivity and protection strategies - Miszczyk, Andrzej; Szociński, Michał; Darowicki, Kazimierz (Chemical and Process Engineering: New Frontiers, 2026)
Although composting is a mature and economically favorable waste treatment technology, the controlled aerobic biodegradation of organic waste generates physicochemical conditions that are highly aggressive toward metallic and cementitious materials. This paper examines the corrosive environment in municipal solid waste composting facilities and its implications for material degradation and structural durability. Appropriate corrosion protection strategies were proposed based on the obtained results. The corrosivity of composting atmospheres arises from both chemical and microbiological processes. Elevated temperatures (40–70°C), persistent high relative humidity (>90%), and the presence of condensates enriched with organic acids, ammonia, carbon dioxide, and reduced sulfur compounds create an environment conducive to accelerated corrosion. Operational factors, including condensation–evaporation cycles and acid-laden runoff, accelerate corrosion kinetics and compromise protective coatings. Given the limited empirical data on composting-specific atmospheric corrosivity, the corrosion rate of steel and zinc was determined under the conditions of a real operating composting plant according to the methodology described in the ISO 12944-2 standard and the appropriate corrosivity categories were defined. Based on this, optimized anti-corrosion systems were developed for new and renovated municipal solid waste composting facilities.